(untitled) (CIPEEX, 2022)
IN THE MODERN WORLD OF EDUCATION, STUDENTS HAVE TO DEAL WITH EVER-INCREASING HOURS AND COMPLEX CONTENT. DUE TO THE GREAT DIFFICULTY OF FOLLOWING A FAST PACE AND SUCCEEDING IN THE ACADEMIC WORLD, MANY STUDENTS ARE LOOKING FOR WAYS TO HELP. ONE OF THE MOST USED MEANS TO TRY TO INCREASE THEIR COGNITIVE CAPACITY IS THE NON-PRESCRIPTION USE OF PSYCHOSTIMULANTS, LIKE METHYLPHENIDATO. CROSS-SECTIONAL STUDIES SUGGEST THAT THESE DRUGS MAY CAUSE CHEMICAL AND PSYCHOLOGICAL DEPENDENCE. THIS PRE-RESEARCH PROJECT WILL INVESTIGATE THE USE OF METHYLPHENIDATE IN MEDICAL STUDENTS FROM THE 1ST TO 12TH PERIOD OF THE CENTRO UNIVERSITÁRIO DE ANÁPOLIS - UNIEVANGLICA, TO COLLECT EPIDEMIOLOGICAL DATA (PERIOD, SEX AND AGE), INCIDENCE OF DRUG USE, OF USE (PRESCRIBED OR NOT PRESCRIBED), SIDE EFFECTS AND TO VERIFY IF THERE WAS IMPROVEMENT OF THE ACADEMIC PERFORMANCE AFTER THE USE. THE RESEARCH WILL BE OF A QUASI-EXPERIMENTAL TYPE WITH DESCRIPTIVE AND CORRELATIONAL DESIGN AND THE STUDY WILL BE CONSTRUCTED BY MEANS OF A CONVENIENCE SAMPLE WITH ALL MEDICAL STUDENTS FROM THE FIRST (1ST) TO THE TWELFTH (12TH) PERIODS THAT AGREE TO PARTICIPATE IN THE RESEARCH, THUS, THERE WILL BE NO NEED FOR SAMPLE CALCULATION. IT IS ESTIMATED THE PARTICIPATION OF 500 INDIVIDUALS. WE WILL USE AS A RESEARCH TOOL THE QUESTIONNAIRE THE INDISCRIMINATE USE OF METHYLPHENIDATE AMONG MEDICINE STUDENTS. IT IS EXPECTED TO FIND AN EXPRESSIVE NUMBER OF NON-PRESCRIPTION METHYLPHENIDATE CONSUMPTION, ASSOCIATED TO THE SEARCH FOR IMPROVEMENT IN ACADEMIC PERFORMANCE. CONCOMITANT TO THIS, IT IS ASSUMED AN INCREASE IN THE INCIDENCE OF SIDE EFFECTS WITH THE USE OF THE DRUG.